Maleficent As an Affectionate Fey in Disney’s 2019 Maleficent: Mistress of Evil - Ni Komang Arie Suwastini; Ni Putu Diah Setyadewi; I Nyoman Pasek Hadi Saputra; Ni Nyoman Artini; I Gusti Ngurah Agung Wijaya Mahardika (Faculty of Humanities, Diponegoro University, 2022)
Although Maleficent’s characterizations as wicked witch by the first Disney’s adaptation into Maleficent in 2014, the beginning of the 2019 sequel Maleficent: Mistress of Evil started with a prologue that Maleficent was narratively still considered evil, from which the plot evolves to reveal how the marginalizing characterization prevailed. Amidst this entanglement between the film’s plot and Maleficent’s character revelation, the present study aimed at elaborating Maleficent’s characterizations as an affectionate fey. The present study employed McKee’s (2003) textual analysis to observe Maleficent’s characterizations along the plot development, to reveal how the film portray Maleficent’s affectionate dispositions despite her formidable strength and appearance. The study concludes that Maleficent affections are highlighted through her actions toward the moors and the marginalized, as well as her blessings for Prince Phillip, underlining her willingness to admit her misjudgment and to repent because of her love for Aurora. This finding implies that the film’s plot development strongly relies on Maleficent’s character development facilitated by her strong affection as a surrogate mother.Although Maleficent’s character as a wicked witch has been deconstructed by the first Disney's adaptation of Maleficent in 2014, the beginning of the 2019 sequel Maleficent: Mistress of Evil started with a prologue that Maleficent was narratively still considered evil, from which the plot evolves to reveal how her marginalizing traits prevailed. Amidst this entanglement between the film's plot and Maleficent's character revelation, the present study aimed at elaborating on Maleficent's personality as an affectionate fey. The present study employed McKee’s (2003) textual analysis to observe Maleficent’s character development along the plot development to reveal how the film portrays Maleficent's growing affectionate dispositions despite her formidable strength and appearance. The study concludes that Maleficent's affections are highlighted through her loving, nurturing, and protective traits toward Aurora, the creatures of the Moors, other feys, and humans. With the depiction of these traits, Maleficent emerged as an affectionate Fey in human's eyes. They eliminate the prejudice against Maleficent, the feys, and the fairies, fostering a harmonious life between humans, the feys, and the fairies.